Entrepreneurial education and intention: fear of failure, self-efficacy and gender - Duong, Cong Doanh; Vu, Ngoc Xuan (Journal of small business and enterprise development, 2024)
PurposeThis research adopts the social cognitive career theory (SCCT) and a moderated mediation model to investigate the moderating impacts of entrepreneurial fear of failure (FOF) and gender on the direct and mediation relationships between entrepreneurial education (EE), entrepreneurial self-efficacy (ESE) and entrepreneurial intention (EI).Design/methodology/approachThe authors utilized a three-phase random sampling to compile a dataset from 1,890 graduate students from nine universities and higher education institutions in Vietnam. Cronbach's alpha and confirmatory factor analysis results showed that the key study variables were reliable and valid. Harman's single-factor method and other tests of analysis assumptions ruled out common method bias and other confounding factors. The authors utilized the PROCESS macro to test a hypothesized moderated mediation model that included direct, indirect and conditional indirect effects.FindingsThe findings yield that ESE partially and positively mediates the relation between EE and EI. FOF was found to negatively moderate the impacts of EE on ESE and EI, and the direct effect of ESE on EI among females is stronger than among males. More importantly, the mediation influence of FOF on the linkage between EE and EI becomes weaker when the level of FOF is high, yet this mediation relationship among females is higher than among males at all levels of FOF.Practical implicationsThe results of this research are valuable for educators, policymakers and practitioners so that they may inspire individuals' entrepreneurial pursuits, especially those of female entrepreneurs.Originality/valueThis study significantly contributes to the entrepreneurship and gender literature by applying the SCCT to elucidate the moderated mediation impacts of FOF, ESE and gender on the relationship between EE and EI.